PROMOTING STUDENTS’ GOOD CHARACTERS AND IMPROVING THE STUDENTS’ WRITING SKILL THROUGH INDONESIAN CULTURE-BASED STORY - Entika Fani Prastikawati; Th. Cicik Shopia B (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2014)
This article focused on improving student’s writing skill and promoting students’ good character through Indonesian culture-based story. The objectives are to know how Indonesian culture-based story gives contribution in promoting students’ good characters and improves student’s writing skill in the second semester students of IKIP PGRI Semarang. This study useD true experimental design. The population is the second semester students of IKIP PGRI Semarang. Then, the samples are 67 students as the samples. The instrument of this study are questionnaire and test; which are given as pre-test and post-test. The goal of questionnaire is to know the students’ reflection of good character and the aim of test is to measure the student’s writing skill of the second semester of IKIP PGRI Semarang. Based on data analysis, there were some significance improvements of the student’s score both of students’ reflection of good character and student’s writing skill. It means that Indonesian culture-based story can promote students’ good character and also improve students’ writing skill. From the result of this study, the writer concludes that using Indonesian culture-based story as material is effective and had good effect of students’ good characters and also improve students’ writing skill. Then, this study is expected to be useful for the teachers/lecturers, students, and the readers. The writer proposes to use Indonesian culture-based story as an alternative material in promoting students’ good character and to improve students’ writing skill. Keywords: Indonesian culture-based story, good characters, writing skill